YC-1 Inhibits VEGF and Inflammatory Mediators Expression on Experimental Central Retinal Vein Occlusion in Rhesus Monkey. (3rd April 2018) - Yan, Zhipeng; An, Jianbin; Shang, Qingli; Zhou, Nalei; Ma, Jingxue
ABSTRACT: Purposes : To investigate the therapeutic potential of YC-1 for experimental central retinal vein occlusion (CRVO) of rhesus monkey. Methods : Six adult rhesus monkeys were recruited in this study. Laser-induced CRVO was established in both eyes of all subjects. Intravitreal injection of YC-1 90 μl (200 μM with 0.01% dimethyl sulfoxide (DMSO) as vehicle) was administrated in right eye and 0.01% DMSO 90 μl in left eye respectively at 1 week after CRVO established. All eyes underwent routine examination at 1 day, 1 week, 2 week, and 1 month after intravitreal injection of YC-1 or DMSO. Meanwhile, vitreous fluid was collected at each time points to analyze concentration of VEGF, HIF-1α, IL-6, IL-8, and MCP-1 mediators by CBA or ELASA method. Results : The experimental CRVO was successfully established in six rhesus monkeys. As expected, the thickness of macular edema significantly decreased at 1 week and 2 weeks after YC-1 injection compared with that of DMSO injection. Subsequently, the central macular thickness in all eyes was recovered to the initial levels at 1 month after photocoagulation. Intraocular pressure (IOP) was not significantly different between two groups during all follow up. Meanwhile, the concentration of IL-6, IL-8, VEGF, and HIF-1α in vitreous fluid significantly decreased after YC-1 injection compared with that of DMSO injection, MCP-1 was not significantly different between both groups. Conclusions : Intravitreal injection of YC-1 significantly alleviated macular edema compared with that of DMSO control group. Meanwhile, both inflammatory factors and angiogenesis-related factors expression were inhibited in vitreous by YC-1 injection.